A compact difference scheme for a two dimensional nonlinear fractional Klein–Gordon equation in polar coordinates. (June 2016) - Wang, Zhibo; Vong, Seakweng
Abstract: In this paper, a high order finite difference scheme for a two dimensional nonlinear fractional Klein–Gordon equation in polar coordinates is proposed. The difficulty caused by the variable coefficient and the nonlinear term in the equation is carefully handled. Stability and convergence are analyzed using the matrix form of the scheme. Numerical examples are provided to demonstrate the theoretical results.